Analisis Laporan Keuangan Pemerintahan dalam Kondisi Krisis (Emergency) - , Rita Wijayanti; , Prof. Dr. Indra Bastian, MBA., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine whether the financial statement analysis and techniques of governments can produce useful information as a basis for public decision-making, especially economic policy. The research was done because there are many facts which show that governments often fail in making economic policy. Authors propose an alternative technology as a form of solving existing problems, namely the analysis of Flow of Funds. Flow of Funds usefulness of the technology was tested with simulation techniques. Research conducted on the United States government financial statements and Flow of Funds. This study took the events of the economic crisis that struck the United States in the fourth quarter 2008 to third quarter 2009. Study period was taken during the year 2006-2010 covering the crisis, before, and after the crisis. The simulation results show that the analysis of Flow of Funds able to describe the condition, performance, and resource capacity across all sectors of economic actors as well as the influence of economic conditions on economic activity so as to produce useful information in the public decision making, especially economic policy.